Hubungan Pengetahuan dan Sikap Ibu Terhadap Imunisasi Campak Lanjutan Di Wilayah Kerja Puskesmas Tapaktuan Aceh Selatan - Rasinta, Ayu; Alamsyah, T.; Murdani, Ihsan; Nursia N, Lili Eky; Rimonda, Rubi (Yayasan Jompa Research and Development, 2025)
Measles is a dangerous infectious disease with serious complications, yet follow-up immunization coverage in Indonesia, particularly in South Aceh, remains low. In the Tapaktuan Primary Healthcare Center's catchment area, follow-up measles immunization coverage was only 8.2% in 2023, accompanied by an increase in suspected cases. This study aims to determine the relationship between mothers' knowledge and attitudes regarding the provision of follow-up measles immunization in the area. This research employed an analytical correlational approach with a cross-sectional design. The study population comprised all mothers with children aged 24-59 months residing in the Tapaktuan Primary Healthcare Center's catchment area, totaling 338 respondents. The sample size was determined using Slovin's formula, yielding 78 respondents selected through proportional random sampling from 8 villages within the Tapaktuan Primary Healthcare Center's catchment area. Data were collected using questionnaires and analyzed through univariate and bivariate analysis with Chi-Square tests. The bivariate analysis results demonstrated statistically significant relationships between knowledge and the provision of follow-up measles immunization (p = 0.001; OR = 6.706) and between attitude and the provision of follow-up measles immunization (p = 0.006; OR = 4.500). Therefore, it can be concluded that there are significant relationships between mothers' knowledge and attitudes regarding the provision of follow-up measles immunization. These findings are associative in nature and cannot be interpreted as causal relationships due to the limitations of the cross-sectional design.